Islam Politics in Soeharto Era (1968-1998) - Hakim, Masykur (Ar-Raniry: International Journal of Islamic Studies, 2015)
HMI wasÂ  founded on February 4, 1947, in Yogyakarta town when Indonesian nation was in the midst of struggle for defense of independent proclamation from the menace Dutch colonialism which was trying to reoccupy the country.Several Muslim University student studying in Sekolah Tinggi Islam (STI, Islamic High School) felt inspired to establish a Muslim student organization, letter called âHimpunan Mahasiswa Islamâ (HMI, or Muslim University Student Association). One of the was Lafran Fane who was regarded the founding father of HMI. They were highly concerned over the problems of Muslim community, particularly, the Muslim University students. Also they had aÂ  commitment to the problem facing the entire Indonesian people.The objective of HMI was put forward first by Lafran Fane on the association oh âPersatuan Pelajar Indonesiaâ (PPI, or Islamic Student Union) conference held in Ponorogo, from 4th to 6th November, 1947. He declared.As a coordination institution that called upon the student to study and comprehend the Islamic doctrine. As scholar and citizen they should have balance of duty between here and hereafter. Reason and emotion, faith and knowledge and they should be ready to face the menace originated from western education system. Islam should flourish at mass level and spread among student masses outside of the STI.Â